Therapeutic Hypothermia Inhibits the Classical Complement Pathway in a Rat Model of Neonatal Hypoxic-Ischemic Encephalopathy - Shah, Tushar A.; Pallera, Haree K.; Kaszowski, Cortney L.; Bass, William Thomas; Lattanzio, Frank A. (Frontiers in Neuroscience, 2021)
Objective Complement activation is instrumental in the pathogenesis of Hypoxic-ischemic encephalopathy (HIE), a significant cause of neonatal mortality and disability worldwide. Therapeutic hypothermia (HT), the only available treatment for HIE, only modestly improves outcomes. Complement modulation as a therapeutic adjunct to HT has been considered, but is challenging due to the wide-ranging role of the complement system in neuroinflammation, homeostasis and neurogenesis in the developing brain. We sought to identify potential therapeutic targets by measuring the impact of treatment with HT on complement effector expression in neurons and glia in neonatal HIE, with particular emphasis on the interactions between microglia and C1q. Methods The Vannucci model was used to induce HIE in term-equivalent rat pups. At P10-12, pups were randomly assigned to three different treatment groups: Sham (control), normothermia (NT), and hypothermia (HT) treatment. Local and systemic complement expression and neuronal apoptosis were measured by ELISA, TUNEL and immunofluorescence labeling, and differences compared between groups. Results Treatment with HT is associated with decreased systemic and microglial expression of C1q, decreased systemic C5a levels, and decreased microglial and neuronal deposition of C3 and C9. The effect of HT on cytokines was variable with decreased expression of pro and anti-inflammatory effectors. HT treatment was associated with decreased C1q binding on cells undergoing apoptosis. Conclusion Our data demonstrate the extreme complexity of the immune response in neonatal HIE. We propose modulation of downstream effectors C3a and C5a as a therapeutic adjunct to HT to enhance neuroprotection in the developing brain.